Safety and pharmacokinetics of medical cannabis preparation in a monocentric series of young patients with drug resistant epilepsy. (June 2020) - Gherzi, Marcella; Milano, Giulia; Fucile, Carmen; Calevo, Maria Grazia; Mancardi, Maria Margherita; Nobili, Lino; Astuni, Pietro; Marini, Valeria; Barco, Sebastiano; Cangemi, Giuliana; Manfredini, Luca; Mattioli, Francesca; et al.
Highlights: Prospective open trial with a galenic preparation (decoction) of medical cannabis. Range THC 5.2–7.2 %, CBD 8.2–11.1 %, CBD dose titration (from 0.7 to 4.4 mg/kg/day). Good safety profile in add-on for young patients with drug-resistant epilepsy. THC and CBD plasma concentrations correlated with their administered dosages. Need of a therapeutic drug monitoring for cannabinoids therapy, with UHPLC–MS/MS. Abstract: Objectives: To evaluate safety and pharmacokinetic parameters (PK) of medical cannabis in add-on for children and young adults with drug-resistant epilepsy. Design, setting: Ten patients (4 females, 6 males, age 2.5–23.2 years) were enrolled in a prospective open trial with a galenic preparation (decoction) of Italian cannabis (FM2, ratio THC:CBD = 3:5, range THC 5.2–7.2 %; CBD 8.2–11.1 %). Patients received the first dose in Hospital, progressively augmented by CBD dose titration (from 1 to 4 mg/kg/day). Outcome measures: In order to assess safety, blood parameters, heart rates and electrocardiograms (ECGs) were evaluated before the enrollment and during the follow up. The PK study was performed measuring THC and CBD concentrations by UHPLC–MS/MS in plasma samples collected during the first administration and at each follow-up visit. Results: Two out of ten patients stopped the treatment for adverse events (detected in 6/10: gastroenteric, sleep or behavioral disorders) and difficulties in drug supply. We observed minor ECG alterations in two patients and asymptomatic transient reductions of fibrinogen after 6 months of therapy. The PK study during follow-up revealed statistically significant correlations between THC-CBD blood concentrations and: volumes of decoction, FM2 and THC-CBD daily dosages. Conclusions: The present study, although with some limitations, shows a good safety profile of medical cannabis in children and young patients with drug-resistant epilepsy and encourages the possibility of further studies with oral cannabis-based drugs. The correlations between THC-CBD plasma concentrations and their administered dosages underline the need of a therapeutic drug monitoring for cannabinoids therapy.